Implementation of Occupational Safety and Health (OSH) through the SAPA Program (Awareness of Potential and Safe Production) in UMKM Rengginan X - Erliana Nur Azizah (Departemen K3 FKM Universitas Halu Oleo, 2026)
Occupational safety and health (OSH) is an important component that must be considered in various business sectors, including the home-based food industry managed by Micro, Small and Medium Enterprises (MSMEs). Rengginan X MSME is one of the micro businesses that has a production process with significant potential hazards, especially related to processing, frying, and handling food ingredients without using safe procedures. Initial observations indicate that non-ergonomic work positions, low use of personal protective equipment (PPE), and substandard food sanitation practices are some of the conditions that can endanger workers. This forms the basis for the implementation of the SAPA (Aware of Potential and Safe Production) Program to improve OSH understanding and practices in MSMEs. The purpose of this study is to determine the effectiveness of the SAPA Program in increasing understanding of hazards, the implementation of safe production standard operating procedures (SOPs), and changes in the behavior of Rengginan MSME workers. This study used qualitative research with a case study design. There were 20 informants consisting of owners and workers of Rengginan MSMEs. K3 observation sheets, semi-structured interview guidelines, and checklists for the implementation of standard operating procedures (SOPs) for safe production were part of the research instruments. Thematic analysis was used to examine changes in OSH understanding, attitudes, and practices before and after the assistance program. The results showed that workers had a better understanding of potential occupational hazards, more ergonomic work layouts, and greater compliance with the use of PPE and the implementation of safe production SOPs. Furthermore, through education, direct mentoring, and the habit formation of OSH practices, the SAPA program was demonstrated as an easy-to-implement OSH intervention model for small and medium-sized MSMEs.